The Shift Process in Transitivity System on Obama’s and Trump’s Inauguration Speech: A Translation Study - Taufik Nur Hidayat; M.R. Nababan; Djatmika Djatmika (Humaniora, 2019)
The purpose of this study is to describe the shift process which is caused by applying certain translation techniques. The techniques are modulation, transposition, implication, and reduction by Molina and Albir (2002). The research used descriptive qualitative-quantitative method by applying purposive sampling technique. The source of the data was the text of Obama’s and Trump’s inauguration speech and their respective translations. There were 152 data in each inauguration speech. The data were the clause which contains the process type which is realized in verbal group in English and its translation. Based on the total of research data, 10 data or 6.57 % in Obama’s inauguration speech and 7 data or 4.60 % in Trump’s inauguration speech was obtained. The obtained data was changing or shifting in process type from the original text into the target text (Indonesian). So, the result of the research supports the theory that modulation, implication, explication, and reduction can cause the shift, especially in verbal group.